Rapid atrophy of cardiac left ventricular mass in patients with non‐small cell carcinoma of the lung. Issue 5 (10th July 2019) - Kazemi‐Bajestani, Seyyed Mohammad Reza; Becher, Harald; Butts, Charles; Basappa, Naveen S.; Smylie, Michael; Joy, Anil Abraham; Sangha, Randeep; Gallivan, Andrea; Kavsak, Peter; Chu, Quincy; Baracos, Vickie E.
Abstract: Background: Cancer is a systemic catabolic condition affecting skeletal muscle and fat. We aimed to determine whether cardiac atrophy occurs in this condition and assess its association with cardiac function, symptoms, and clinical outcomes. Methods: Treatment naïve metastatic non‐small cell lung cancer patients ( n = 50) were assessed prior to and 4 months after commencement of carboplatin‐based palliative chemotherapy. Methods included echocardiography for left ventricular mass (LVM) and LV function [LV ejection fraction, global longitudinal strain (GLS), diastolic function], computed tomography to quantify skeletal muscle and total adipose tissue, Eastern Cooperative Oncology Group Performance Status (ECOG‐PS), validated questionnaires for dyspnoea and fatigue, plasma biomarkers, tumour response to therapy, and overall survival. Results: During 112 ± 6 days, the median change in LVM was −8.9% [95% confidence interval (95% CI) −10.8 to −4.8, P < 0.001]. Quartiles of LVM loss were −20.1%, −12.9%, −4.8%, and +5.5%. Losses of muscle, adipose tissue, and LVM were frequently concurrent; LVM loss > median value was associated with loss of skeletal muscle [odds ratio (OR) = 4.5, 95% CI: 1.4–14.8, P=0.01] and loss of total adipose tissue (OR = 10.0, 95% CI: 2.7–36.7, P < 0.001). LVM loss was associated with decreased GLS (OR = 6.6, 95% CI: 1.9–22.7, P=0.003) but not with LV ejection fraction or diastolic function. In the population overall, plasma levels of C‐reactive protein (P=0.008), high sensitivity troponin T (hs‐TnT) (P=0.03), and galectin‐3 (P=0.02) increased over time, while N‐terminal pro B‐type natriuretic peptide and hs‐cTnI did not change over time. C‐reactive protein was the only biomarker associated with LVM loss but at the univariate level only. Independent predictors of LVM loss were prior weight loss (adjusted OR = 10.2, 95% CI: 2.2–46.9, P=0.003) and tumour progression (adjusted OR = 14.6, 95% CI: 1.4–153.9, P=0.02). LVM loss was associated with exacerbations of fatigue (OR = 6.6, 95% CI: 1.9–22.7, P=0.003), dyspnoea (OR = 9.3, 95% CI: 2.4–35.8, P<0.001), and deterioration of performance status (OR = 4.8, 95% CI: 1.3–18.3, P=0.02). Patients with concurrent loss of LVM, skeletal muscle, and fat were more likely to deteriorate in all three symptom domains and to have reduced survival (P=0.05). Conclusions: Intense LVM atrophy is associated with non‐small cell lung cancer‐induced cachexia. Loss of LVM was associated with emerging alterations of GLS, indicating subtle changes in left ventricular function. Longer term studies are needed to assess the full scope of cardiac atrophy and its impact. LVM atrophy arises in conjunction with losses of fat and skeletal muscle and is temporally associated with meaningful declines in performance status, worsening of fatigue, and dyspnoea, as well as poorer tumour response and decreased survival. The specific contribution of LVM atrophy to these outcomes requires further study.